2011
DOI: 10.1007/s12011-011-9166-y
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Regulates Gene Expression of Selenoprotein W in Chicken Skeletal Muscle System

Abstract: Selenoprotein W (SelW) is abundantly expressed in skeletal muscles of mammals and necessary for the metabolism of skeletal muscles. However, its expression pattern in skeletal muscle system of birds is still uncovered. Herein, to investigate the distribution of SelW mRNA in chicken skeletal muscle system and its response to different selenium (Se) status, 1-day-old chickens were exposed to various concentrations of Se as sodium selenite in the feed for 35 days. In addition, myoblasts were treated with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[55][56][57] Prior studies indicated that Se deciency inuenced the expressions of 24 selenoproteins, such as Txnrd1, Sels, Selu, Sepx1, Sepw1 in the immune system, pancreas of chickens. [58][59][60] In the present study, we mainly studied the effect of dietary Se status on the expressions of all 24 selenoproteins in pancreas. The supranutritional Se intake increased mRNA levels of most selenoprotein in the chickens.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] Prior studies indicated that Se deciency inuenced the expressions of 24 selenoproteins, such as Txnrd1, Sels, Selu, Sepx1, Sepw1 in the immune system, pancreas of chickens. [58][59][60] In the present study, we mainly studied the effect of dietary Se status on the expressions of all 24 selenoproteins in pancreas. The supranutritional Se intake increased mRNA levels of most selenoprotein in the chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium has been recognized as a nutritional essential trace element that is important in many biological processes in mammals and birds (Holben and Smith, 1999;Surai, 2000). It has a crucial role in embryonic and postnatal development (Surai, 2000;Fortier et al, 2012), immunity, reproduction, antioxidant system (Choct et al, 2004;Juniper et al, 2011), and muscle function (Ruan et al, 2012;Zhang et al, 2012) and is known as a natural antioxidant (Surai, 2002). In poultry as well as in other animal species, Se can be added to diets through its mineral or organic forms, which represent the crucial factor that determines its metabolic fate (Suzuki, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SelW mRNA expression in the gastrointestinal tract, liver, pancreatic tissue; immune organs and skeletal muscle system in chickens are highly sensitive to Se supply (Li et al 2010;Gao et al 2011;Sun et al 2011;Wang et al 2011;Yu et al 2011;Ruan et al 2011). Pagmantidis et al (2005) reported that SelN and SelW expression levels in human intestinal Caco-2 cells is highly sensitive to Se-depletion and Seadequate conditions.…”
Section: Discussionmentioning
confidence: 99%